2005
DOI: 10.1016/j.femsle.2005.07.024
|View full text |Cite
|
Sign up to set email alerts
|

LexA, a transcription regulator binding in the promoter region of the bidirectional hydrogenase in the cyanobacteriumSynechocystissp. PCC 6803

Abstract: The unicellular cyanobacterium Synechocystis PCC 6803 contains a single pentameric bidirectional hydrogenase encoded by hoxEFUYH. Transcriptional experiments demonstrated that the five hox genes are part of a single transcript together with three ORFs with unknown functions. The transcription start point was localized by 5' RACE to 168bp upstream the hoxE ATG start codon. DNA affinity assays demonstrated a specific interaction between the hox regulatory promoter region and a protein which, using mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(94 citation statements)
references
References 25 publications
3
90
0
1
Order By: Relevance
“…One correlation is between the gene encoding the LexA-like protein (Sll1626) and the hox operon, these genes were upregulated after the transition to low O 2 . This was consistent with the finding that Sll1626 interacts with the hox promoter and positively regulates its expression (Oliveira & Lindblad, 2005). The genes encoding Sll0359 and Sll0882 are also regulators of the hox operon (Ishii & Hihara, 2008;Oliveira & Lindblad, 2008), these genes are not upregulated under low-oxygen conditions, but may play a role in regulation.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…One correlation is between the gene encoding the LexA-like protein (Sll1626) and the hox operon, these genes were upregulated after the transition to low O 2 . This was consistent with the finding that Sll1626 interacts with the hox promoter and positively regulates its expression (Oliveira & Lindblad, 2005). The genes encoding Sll0359 and Sll0882 are also regulators of the hox operon (Ishii & Hihara, 2008;Oliveira & Lindblad, 2008), these genes are not upregulated under low-oxygen conditions, but may play a role in regulation.…”
Section: Resultssupporting
confidence: 90%
“…The LexA-like protein binds two sites in the hydrogenase (hox) operon and may function as a transcription activator (Gutekunst et al, 2005;Oliveira & Lindblad, 2005). Consistent with this, we observed that transcript levels of the hox operon (sll1220-sll1226) increased in both strains under low oxygen (Table 2).…”
Section: The Absence Of Hik31 Alters Transcriptional Response To Low supporting
confidence: 79%
“…4 shows the hydrogenase operon which encodes all proteins required for pentameric bidirectional Ni-Fe hydrogenase (HoxEFUYH). This operon uses a single TSS located 168 nt upstream of hoxE (19), and its regulation is well studied (19)(20)(21). Intriguingly, we found that the operon is framed by two highly expressed ncRNAs, one of which [SyR1 (14)], was strongly upregulated under high light, whereas the other (ncr0700) was maximally expressed in the dark (Fig.…”
Section: Resultsmentioning
confidence: 62%
“…In Synechocystis sp. PCC 6803, the hoxEFUYH genes are cotranscribed, with the transcription start point located 168 bp upstream of the start codon (87,158). Taking the high diversity of the different cyanobacterial species into account, expression of the bidirectional hydrogenase in cyanobacteria seems to be species specific.…”
Section: Hydrogenases In Cyanobacteria Hydrogenase Types In Cyanobactmentioning
confidence: 99%